Hospital-Based Cancer Incidence in Nepal from 2010 to 2013 - Poudel, Krishna Kanta; Huang, Zhibi; Neupane, Prakash Raj; Steel, Roberta; Poudel, Janaki Kharel (Nepal Journal of Epidemiology, 2017)
Background: Cancer is one of the leading causes of death throughout the world. Analyzing the incidence of cancer by site, sex and age is essential to detect the burden of cancer. Throughout the twelve hospital based cancer registries of Nepal, a total of 29,802 cancer cases with known age, were registered from January 1st 2010 to 2013 December 31st. The purpose of this retrospective study is to present the incidence of all cancer sites in both males and females for this period. Materials and Methods: This paper reviews data from all the hospital based cancer registries over a four-year period. This retrospective study has illustrated the number of cases, frequencies and crude incidence of all cancers by sex and site. For statistical analysis, SPSS (version 23.0) and Microsoft Excel 2010 were used. Results: Over the four-year period from January 1st 2010 to 2013 December 31st the major cancer in males was identified as follows: lung cancer (17.5%) followed by stomach cancer (7.6 %) and larynx cancer (5.4%). Among females, for the same four-year period, the three common cancers were identified as cervix (18.9 %) followed by breast (15.6 %) and lung (10.2%). Conclusion: This retrospective study concluded that cancer is being increased by calendar years both in males and females however, the incidence of cancer is higher in females compared to males.